Characterization of local goats of Chhattisgarh plains - BHUARYA, SHEETAL; MUKHERJEE, K; SINGH, MOHAN; PARVEEN, KAISER (The Indian Journal of Animal Sciences, 2014)
There are 23 descript breeds of goat in India. However there is no recognized breed of goat registered by Chhattisgarh state hence requires systematic study for their characterization. The present study was undertaken to establish the norms of different physical characteristics, reproductive and productive performance traits and haematological profile of local goats of Chhattisgarh plains. Information was collected from Raipur, Durg, Rajnandgaon and Kanker districts of Chhattisgarh plain region. The average measurement for body weight, body length, height, ear length, face length, horn length and tail length for adult male were 31.05±0.49kg, 71.26±0.6, 74.44±0.91, 45.35±0.71, 16.14±0.21, 19.47± 0.18, 15.85±0.43 and 16.05 cm respectively. The corresponding values in adult female were 24.55±0.47 kg, 61.13±0.90, 64.74±0.73, 37.37±0.52, 15.74±0.24, 18.41±0.18, 11.72±0.57, and 14.58±0.22 cm respectively. The mean values for the reproductive performance traits i.e. age at first mating in male, age at first mating in female, age at first kidding and kidding interval were observed as 184±0.05, 216±0.04, 370±0.4 and 184±0.03 days, respectively, and average litter size 1.5. The mean values for the productive performance traits daily milk yield, total lactation milk yield and lactation length were recorded as 307.25±13.16 ml, 32.29±2.65 litres, and 105.75±2.48 days, respectively. Different haematological parameters such as haemoglobin, packed cell volume, total erythrocytes count, total leukocytes count, mean corpuscular haemoglobin, mean corpuscular volume and mean corpuscular haemoglobin concentration were considered and value estimated as 9.35±0.20 (g%), 28.9±0.66 (%), 8.45+0.17 (million/μl), 9,660±256.33 (thousand/μl), 9.1± 0.22 (pg), 27.79±0.0 (fl), and 32.39±0.27(%) respectively. Hence this study was aimed to phenotypically characterize the local goat in view of establishing a database for the breed and undertaking conservation programme for preserving rich indigenous genetic resources biodiversity.